The Penerapan Metode Pembelajaran Crossword Puzzle (Teka-Teki Silang) untuk Meningkatkan Hasil Belajar Biologi Peserta Didik di SMAN 6 Mataram - Khairunnufus, Nastri; Artayasa, I Putu; Yasa, I Komang Mudika (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
Crossword Puzzle are a fun learning method. This method can involve active participation from students from the beginning of the learning process so that students do not lose the essence of ongoing learning. This strategy can create active learning strengthen concepts, and improve learning outcomes. This collaborative classroom action research aims to improve the learning outcomes of students in class. Data collection techniques through observation and written tests (cognitive). This research was conducted in two cycles, each cycle consisting of planning, action, observation, and reflection. Data analysis uses qualitative descriptive analysis. The research results show that the application of the TTS learning method can improve the learning outcomes of class X.7 students at SMA Negeri 6 Mataram for the 2022/2023 academic year. This can be seen from the average value of learning outcomes in cycle I of 86 with classical completeness of 77% (high category) and in cycle II there was an increase with average learning outcomes of 87 with classical completeness of 85% (very high category). Keywords : Learning Methods, Crossword Puzzle, Learning Outcomes